CROSS-BORDER COOPERATION MECHANISMS AND HUMAN POTENTIAL: STRATEGIC INTERACTION - PITYULYCH, Mykhaylo; KUBINIY, Nataliya; TIZESH, Pavlo (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study aims to study the interaction of cross-border cooperation mechanisms and the human potential of cooperating regions. To achieve the goal, the following tasks were solved: 1. A comparative characteristic of the level of development of the EU countries bordering Ukraine is presented. 2. The main mechanisms of TCC are outlined. Cross-border cooperation is essential to economic development, strengthening relationships between countries and territories located on borders. Cross-border collaboration is one factor in building sustainable competitive advantages for regions involved in cooperation, thereby affecting human potential. In turn, improving the quality of human potential is a competitive advantage that allows for the further development of territories. Among the wide range of mechanisms for activating cross-border cooperation, joint entrepreneurship, clustering in science and innovation, and strategic management are highlighted. Joint entrepreneurship ensures the transfer of knowledge and cultural and social transformations through capitalization and concentration of resources. It also performs other actions that affect the economic growth and human development of regions participating in collaboration. Strategic management expands the range of competencies and develops competencies, affecting human capital. Strategic management is the basis for achieving high results and ensuring the sustainable development of the system through optimal use of the potential of its employees. Clusters also allow for more complete use of regional resources and the formation of a scientific and innovative environment that will promote human development and the formation of strategic competitive advantages. In general, innovation clusters help create conditions for sustainable development, increase living standards, strengthen competitiveness in the global market, and ensure equal opportunities for all population segments. Human potential creates business, carries out managerial efforts, and ensures effective cooperation of entrepreneurial activities, which increases the level of cross-border cooperation.